Comparing Construction and Study of Concept Maps – An Intervention Study on Learning Outcome, Self-Evaluation and Enjoyment Through Training and Learning - Lenski, Sina; Elsner, Stefanie; Großschedl, Jörg (Frontiers in Education, 2022)
Concept maps are graphical tools for organizing and representing knowledge. They are recommended for biology learning to support conceptual thinking. In this study, we compare concept map construction (CM-c, i.e., creating concept maps) and concept map study (CM-s, i.e., observing concept maps). Existing theories and indirect empirical evidence suggest distinct effects of both formats on cognitive, metacognitive and emotional aspects of learning. We developed a CM-c training, a CM-s training, and a brief introduction to concept maps (control training) for junior high school students. We investigated effects on learning performance, concept map quality, cognitive load (cognitive effects), accuracy of self-evaluation (metacognitive effects) and enjoyment (emotional effects) of these trainings in a subsequent learning phase (CM-c learning vs. CM-s learning) in a quasi-experimental two-factorial study with 3 × 2 groups (N = 167), involving the factors training type and learning type. Results reveal that CM-c training increased learning performance and concept map quality. Effects of CM-c training on learning performance transferred onto learning with CM-s. Self-evaluation was slightly more accurate after CM-c training than CM-s training. Students reported moderate, and highly varying enjoyment during CM-c and CM-s learning. The superiority of CM-c over CM-s in learning performance and concept map quality probably lies in its characteristic of being an active learning strategy. We recommend practitioners to favor CM-c training over CM-s training, and foster students’ active engagement and enjoyment.